Barganha e justiça criminal negocial : análise das tendências de expansão dos espaços de consenso no processo penal brasileiro - Vasconcellos, Vinicius Gomes de (2014)
Involved in the concentration area Criminal System and Violence and in the research line Contemporary Criminal Systems, this paper aims to develop a critical analysis of the trends of expanding consensual opportunities in the Brazilian criminal justice, primarily within the introduction of negotiation mechanisms, such as plea bargaining, which, in broad terms, allows the early imposition of the punitive power in the basis of a guilty plea, in exchange of a benefit, a reduction in the punishment. As seen, it represents a strong inclination on the international criminal procedure scene, which is progressively more guided by the goal of procedural acceleration, which actually is going beyond that claim and is leading to justify the imposition of criminal sanctions with no attention to the due process of law rules. After the introductory definition of the guidelines ideas of opportunity and consensus, the main features of plea bargain will be drawn-up, fundamentally from the United States example. Then it will ask the adherence of such mechanisms to the fundaments of criminal procedural systems, besides suggesting some relevant aspects of the international scene in order to demonstrate the extend of the studied trends. On the other hand, considering the current Brazilian scenario, the consensus possibilities, which are allowed within the Juizados Especiais Criminais (Brazilian minor courts) and by the whistleblower award, will be studied. Subsequently we will analyze the legislative proposals currently under discussion at the Brazilian national level (PLS 156/2009 and 236/2012), which have regulations projecting an expansion of the possibilities of agreements between prosecution and defense to immediate imposition of a criminal sanction. Finally, critics will be systematically structured in face of the bargained justice and plea bargaining, revealing their undeniable troubles and inconsistencies that lead to violations of the fundamental premises of criminal procedure in a democratic state. Consequently, it will enforce the importance of a critic viewpoint toward trends of expanding consensual opportunities in criminal justice.